Oxygen stable isotopes of a network of shrubs and trees as high-resolution plaeoclimatic proxies in Northwestern China - Li, Qiang; Liu, Yu; Nakatsuka, Takeshi; Zhang, Qi-Bin; Ohnishi, Keiko; Sakai, Akiko; Kobayashi, Osamu; Pan, Yingnan; Song, Huiming; Liu, Ruoshi; Sun, Changfeng; Fang, Congxi (Agricultural and forest meteorology, 2020)
•δ18O variations of shrub, conifer and broad-leaved trees are highly consistent.•The first principal component of the δ18O variations (PC1) is extracted.•PC1 is significantly correlated with regional summer RH (r = −0.855, p < 0.001, n = 30).•PC1 is related to the atmospheric circulation patterns such as EASM and ENSO. Tree rings play an important role in high-resolution paleoclimate reconstruction over large areas. Nevertheless, the sampling sites of most existing tree-ring networks are unevenly distributed due to the limitations of the availability of appropriate tree species and sampling conditions. In light of the good spatial representation provided by tree-ring stable oxygen isotope ratio (δ18O), we selected several shrubs (Hippophae rhamnoides L.) found in near-glacier valleys, conifer (Picea crassifolia Komarov) trees in alpine meadows, and broad-leaved (Populus euphratica Olivier) trees found in deserts. Although the three sampling sites were each 250–360 km apart, with varied site conditions and very distinct species, we observed coherent variations in the δ18O of the three species within a common time interval. The average correlation coefficient was found to be 0.674 (p < 0.001, n = 30) among annual-ring δ18O series of three species. All annual-ring δ18O of three species demonstrated significant negative correlations with relative humidity (RH) and precipitation, and significant positive correlations with temperature, in spring and summer. The correlation coefficient between the first principal component (PC1) of the δ18O variations in the three species and the regional summer (June to August) RH was found to be −0.855 (p < 0.001, n = 30). In addition, PC1 showed variations similar to those of δ18O in precipitation. Spatial correlation demonstrated that PC1 represents the hydroclimatic variability that occurs in most of central-western China. Significant correlations with sea-level pressure and several East Asian Summer Monsoon indices indicated that PC1 was affected by the large-scale atmospheric circulation pattern and could be used as an indicator of monsoon moisture. PC1 correlated significantly with ten annually resolved hydroclimatic series in central-western China, demonstrating the potential of establishing a tree-ring climate network with uniform spatial distribution using multi-species tree-ring δ18O. The results from these series suggest that an abrupt climate change occurred in 1979. After 1979, PC1 correlated significantly with the summer-season EI Nino Modoki index (r = 0.474, p < 0.02, n = 24). This implied that the effect of the central Pacific ENSO on the variability in monsoon moisture in China became more prominent after the abrupt climate change in 1979.